Neuroleadership dalam Dunia Pendidikan: Strategi Otak untuk Meningkatkan Produktivitas Sumber Daya Manusia di Era Digital - Septiana, Nani; Aimah, Siti (Faculty of Education and Teacher Training of UINSI Samarinda, 2025)
Abstract The rapid development of digital technology requires educational institutions to adapt quickly, including in the management of Human Resources (HR). SMP Plus Darussalam faces challenges in the form of low teacher productivity, high levels of work stress, and lack of adaptation to technology. To overcome this, the school applies a neuroscience-based leadership approach (neuroleadership) as a strategy to strengthen Human Resources (HR) management. This study aims to analyze the application of neuroleadership in increasing Human Resources (HR) productivity in the digital era, using a qualitative approach through a case study design. Data were collected through in-depth interviews, participant observation, and documentation, and analyzed using the Miles and Huberman interactive model and triangulation of sources and methods. The results of the study indicate that the school designed a neuroscience-based Human Resources (HR) development policy, including training for principals and teachers on emotional regulation, social relationships, and stress management. The principal applies a leadership strategy that supports work autonomy, empathetic communication, and a positive work atmosphere. Teachers experience increased productivity, creativity, and engagement in technological innovation. This study provides theoretical and practical contributions to the development of neuroscience-based leadership that is relevant to educational and modern organizations. Keywords: Neuroleadership, Brain Strategy, Human Resources, Digital Era Abstrak Perkembangan teknologi digital yang pesat menuntut lembaga pendidikan untuk beradaptasi secara cepat, termasuk dalam pengelolaan Sumber Daya Manusia (SDM). SMP Plus Darussalam menghadapi tantangan berupa rendahnya produktivitas guru, tingginya tingkat stres kerja, dan kurangnya adaptasi terhadap teknologi. Untuk mengatasi hal tersebut, sekolah menerapkan pendekatan kepemimpinan berbasis neurosains (neuroleadership) sebagai strategi penguatan manajemen Sumber Daya Manusia (SDM). Penelitian ini bertujuan untuk menganalisis penerapan neuroleadership dalam meningkatkan produktivitas Sumber Daya Manusia (SDM) di era digital, dengan menggunakan pendekatan kualitatif melalui desain studi kasus. Data dikumpulkan melalui wawancara mendalam, observasi partisipan, dan dokumentasi, serta dianalisis dengan model interaktif Miles dan Huberman dan triangulasi sumber dan metode. Hasil penelitian menunjukkan bahwa sekolah merancang kebijakan pengembangan Sumber Daya Manusia (SDM) berbasis neurosains, termasuk pelatihan kepala sekolah dan guru mengenai regulasi emosi, hubungan sosial, dan manajemen stres. Kepala sekolah menerapkan strategi kepemimpinan yang mendukung otonomi kerja, komunikasi empatik, dan suasana kerja yang positif. Guru mengalami peningkatan produktivitas, kreativitas, dan keterlibatan terhadap inovasi teknologi. Penelitian ini memberikan kontribusi teoritis dan praktis dalam pengembangan kepemimpinan berbasis neurosains yang relevan untuk organisasi pendidikan dan modern. Kata Kunci: Neuroleadership, Strategi Otak, Sumber Daya Manusia, Era Digital